2014
DOI: 10.1002/ptr.5173
|View full text |Cite
|
Sign up to set email alerts
|

Guarana (Paullinia cupana Mart.) Prevents β‐Amyloid Aggregation, Generation of Advanced Glycation‐end Products (AGEs), and Acrolein‐Induced Cytotoxicity on Human Neuronal‐Like Cells

Abstract: Advanced glycation end-products (AGEs) are considered potent molecules capable of promoting neuronal cell death and participating in the development of neurodegenerative disorders such as Alzheimer's disease (AD). Previous studies have shown that AGEs exacerbate β-amyloid (Aβ) aggregation and AGE-related cross-links are also detected in senile plaques. Acrolein (ACR) is an α, β-unsaturated aldehyde found in the environment and thermally processed foods, which can additionally be generated through endogenous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…The stimulant effect of guarana is associated with high caffeine content, a psychoactive pseudoalkaloid well known for its benefits to human lifespan and aging-associated neuropathologies [ 4 ]. Guarana also contains other methylxanthines, including theophylline and theobromine, as well as polyphenols, such as catechins and epicatechins [ 5 , 6 ]. This phytochemical composition has been associated with guarana's biological activities, which include antioxidant [ 7 9 ], antimicrobial [ 6 ], and chemoprophylactic activities in carcinogenesis [ 10 , 11 ] and antigenotoxic effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stimulant effect of guarana is associated with high caffeine content, a psychoactive pseudoalkaloid well known for its benefits to human lifespan and aging-associated neuropathologies [ 4 ]. Guarana also contains other methylxanthines, including theophylline and theobromine, as well as polyphenols, such as catechins and epicatechins [ 5 , 6 ]. This phytochemical composition has been associated with guarana's biological activities, which include antioxidant [ 7 9 ], antimicrobial [ 6 ], and chemoprophylactic activities in carcinogenesis [ 10 , 11 ] and antigenotoxic effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in our study, GSP modulated gut microbiota, not only through its major compound caffeine but also because of the presence of polyphenols. With several secondary metabolites, which were previously classified and quantified in GSP (Bittencourt et al, ), gut alterations were more notable, and when could not be identified by analysis, we signed the family or order for taxonomic identification.…”
Section: Resultsmentioning
confidence: 99%
“…Ducke) and caffeine oral administration. Guarana is a nontraditional medicinal plant widely applied in soft drinks, and caffeine is the major compound present in guarana seed powder (GSP; Bittencourt et al, ). GSP is still consumed worldwide for mental fatigue and weight loss (de Oliveira Campos et al, ), tonic for the heart, the kidney, and the liver, antiaging, high cholesterol, intestinal regulation, and many others, as reviewed by Schimpl, da Silva, Gonçalves, and Mazzafera ().…”
Section: Introductionmentioning
confidence: 99%
“…Guarana seed extract (100 and 1000 μg/mL) exerts significant antioxidant capacity as shown by a TRAP assay that was similar to 40 μg/mL of caffeine. In addition, there was a significant reduction of intracellular ROS production in acrolein-induced cytotoxicity on human neuronal-like cells to similar levels in control cells ( p < 0.0001) ( Table 1 ) [ 108 ]. Comparably, Boasquívis et al [ 107 ] demonstrated that 5, 10, and 50 mg/mL of guarana hydroalcoholic extract (GHE), which contains 166.07 μg/mL of caffeine, 36.35 μg/mL of EC, 34.59 μg/mL of catechin, and 2.49 μg/mL of theobromine, has a similar DPPH radical scavenging property as 500 μM of Trolox, a water-soluble analogue of vitamin E. Moreover, either a dose of 10 or 50 mg/mL of GHE markedly reduced intracellular ROS levels in C. elegans models of AD compared to untreated control ( p < 0.05) and eventually prolonged the worm’s lifespan [ 107 ].…”
Section: Free Radicals and Oxidative Damage To Biomoleculesmentioning
confidence: 99%